Antibodies to Mycobacterium paratuberculosis and nine species of environmental mycobacteria in Crohn's disease and control subjects. Issue 3 (March 1993) - Stainsby, K J; Lowes, J R; Allan, R N; Ibbotson, J P
Abstract : Cultural and serological studies have provided limited, often conflicting, evidence of a role for mycobacteria in the pathogenesis of Crohn's disease. Interest has focussed on Mycobacterium paratuberculosis, previously considered to be common in the environment with no major role as a human pathogen. Whether a specific serum antibody response to mycobacteria occurs in Crohn's disease or ulcerative colitis was investigated. Sera from patients with Crohn's disease (n = 38), ulcerative colitis (n = 15), and a healthy control population (n = 30) were assayed in an enzyme linked immunosorbent assay (ELISA) using eight filtered sonicate mycobacterial preparations and a purified protein derivative made from the bovine tubercle bacillus. In addition, IgG, IgM, and IgA levels to M paratuberculosis were determined in sera from patients with active (n = 24) or inactive (n = 29) Crohn's disease and the control populations. There was strong evidence of contact with environmental mycobacteria in all patients and control populations, with the greatest responses to preparations of M avium, M tuberculosis, and M kansasii. A large proportion of patients with Crohn's disease had antibodies that bound most antigens tested but there were no statistical differences between these values and those of the control population. Similarly, there were no differences in antibody levels to M paratuberculosis in patient and control groups. Although a subset of patients with active Crohn's disease (25%) had IgG concentrations that exceeded the control mean by more than 2 SD, this phenomenon may not be specific to Crohn's disease: 20% of a small group of patients with coeliac disease had similarly raised IgG levels to M paratuberculosis. These findings do not provide serological evidence of a role for this organism in the pathogenesis of Crohn's disease.